2017
DOI: 10.1016/j.tet.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

C-Glycosyl 1,2,4-triazoles: Synthesis of the 3-β-d-glucopyranosyl-1,5-disubstituted and 5-β-d-glucopyranosyl-1,3-disubstituted variants

Abstract: Highly variable synthetic routes were elaborated toward trisubstituted C-glycopyranosyl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The analysis of the above‐mentioned sources shows that the structure of triazole derivatives, namely, the nature of the groups combined with a triazole ring is of great significance. As practice shows sometimes for specific cases the development of a new method is required, which is confirmed by literary sources of recent years …”
Section: Introductionmentioning
confidence: 79%
“…The analysis of the above‐mentioned sources shows that the structure of triazole derivatives, namely, the nature of the groups combined with a triazole ring is of great significance. As practice shows sometimes for specific cases the development of a new method is required, which is confirmed by literary sources of recent years …”
Section: Introductionmentioning
confidence: 79%
“…For the synthesis of the necessary 5-β-d-glucopyranosyl-3substituted-1,2,4-triazoles several methods were elaborated (Scheme 1, preparation of the starting compounds was described in the original papers and is not detailed here). Among cyclocondensation routes reactions of amidine 1 or acid chloride 2 with amidrazones gave intermediates 4 and 5, respectively, which on heating gave the expected 1,2,4-triazoles 8 [54]; transformations of tosylamidrazone 7 by acid chlorides [53], or reactions of N-acyl thioamides 10 and 12 with hydrazine [59] also led to 8. A further procedure, representing a new synthesis for 1,2,4-triazoles in general, was based on the bromination of imidoylhydrazones 3 to give the surprisingly stable derivatives 6 which were cyclized to 8 under basic conditions [57].…”
Section: Design and Syntheses Of C-glucopyranosyl Azoles As Glycogen mentioning
confidence: 99%
“…Taking into account the availability of the necessary carbohydrate precursors and reagents routes 3→6→8 and 11→8 are the most advantageous. It is worth noting that the transformations of precursors 10-12 facilitate the syntheses of all regioisomers of trisubstituted C-glucopyranosyl 1,2,4-triazoles, too [59].…”
Section: Design and Syntheses Of C-glucopyranosyl Azoles As Glycogen mentioning
confidence: 99%
“…Among a large number of nitrogen heterocycles, which differ in the size of cycles and the number of heteroatoms, triazoles, and in particular, 1,2,4‐triazoles are of certain interest. Compounds of this class are not found in natural sources, but thanks to the vigorous development of the chemistry of triazoles, in recent years numerous methods for the synthesis of new 1,2,4‐triazole derivatives have been developed ‐ the ones combined with various heterocycles, condensed systems,– and in some cases with the use of microwave radiation.a, Biological research has shown that 1,2,4‐triazoles have a broad spectrum of physiological action: they are antioxidants, insecticides,, inhibitors of p38 MAP kinases, display antimicrobial,, antibacterial,, anticonvulsive,, antitumor,, antifungal, activities, etc.…”
Section: Introductionmentioning
confidence: 99%